Financial and non–financial factors in companies’ adaptation process towards sustainability and sustainable business models - Magdalena Zioło; Elżbieta Szaruga; Anna Spoz (Journal of Entrepreneurship, Management and Innovation)
PURPOSE: The influence of environmental, social, and governance (ESG) factors on financial performance has been confirmed in the literature. The article aims to examine the relationship between financial and non-financial factors in enterprises and to indicate for which groups of enterprises the relationship of ESG and financial performance is most visible in the context of building sustainable business models and the ability to adapt to sustainability. The article assumes that enterprises’ financial and non-financial results determine their adaptability to sustainability, and there is a relationship between financial results, non-financial performance, and companies’ sustainable business models. METHODOLOGY: The analysis encompasses 11 EU countries in the period 2008–2020. The study analyzed 6,864 observations, that is, 96,096 data cells. The data are divided into two groups of variables: financial and non-financial. The research is based on clusters analysis and ANOVA. It was carried out in two stages. In the first step, enterprises were grouped into clusters according to the financial condition criterion, considering the enterprise’s size and sector and country in which it operates. In the next step, it was checked whether enterprises with good financial standing also achieve better non-financial results. FINDINGS: It was found that large enterprises achieve better financial results than small and medium-sized enterprises, even though they operate in the same location and sectors. It can be emphasized there are statistical differences between entities with relatively good financial conditions and those with relatively weaker financial conditions in the context of such values as gender employment gap, total population living in households considering that they suffer from noise, greenhouse gas emission, Corruption Perceptions Index. The companies with relatively better financial standing achieve a smaller gender employment gap (at the national level) than entities with relatively worse financial conditions. It is similar to referring to the greenhouse gas (GHG) level. IMPLICATIONS: The results of this study may be useful for managements of companies in developing strategies of transformation towards sustainability, thanks to the fact that they provide information on what factors should be taken into account in the transformation process. ORIGINALITY AND VALUE: The originality of this study lies in the fact that it takes into account both financial and non-financial factors and examines the relationships between these factors in the process of companies’ adaptation towards sustainability and sustainable business model.